Genetic variation and evolutionary analysis of Pepino mosaic virus in Sicily: insights into the dispersion and epidemiology. (17th August 2016) - Davino, S.; Panno, S.; Iacono, G.; Sabatino, L.; D'Anna, F.; Iapichino, G.; Olmos, A.; Scuderi, G.; Rubio, L.; Tomassoli, L.; Capodici, G.; Martinelli, F.; et al.
Abstract : Pepino mosaic virus (PepMV) is a highly infectious potexvirus that causes a severe disease in tomato ( Solanum lycopersicum ) crops worldwide. In Sicily, the first outbreak was detected in a single greenhouse in 2005 and it was promptly eradicated. However, in 2008, a large number of greenhouses were simultaneously affected, and it was impossible to eradicate or control the virus. This study addressed the dispersion and the genetic diversity of PepMV isolates obtained from the outbreak in Sicily, in comparison with worldwide PepMV isolates, to gain insight into the factors determining the evolution and epidemiology of the virus. A total of 1800 samples from plants with and without symptoms were collected in the Sicilian provinces of Agrigento, Caltanissetta, Palermo, Ragusa, Siracusa and Trapani. Three isolates collected at different times were biologically characterized. The incidence of the virus increased rapidly from 13% in 2011 to 63% in 2013, and phylogenetic analysis showed that all Sicilian isolates of PepMV belonged to the CH2 strain, one of the six strains previously described. Nucleotide diversity of the Sicilian isolates was low, thus suggesting rapid spread and genetic stability.